Impact of Corporate Governance Practices and Firm Performance: An Empirical Study - Venkatraman, Karpagam; Selvam, Murugesan (Indian Journal of Finance, 2014)
Corporate governance (CG) is the process and structure through which the affairs of a firm are managed for enhancing business prosperity and corporate accountability, and the ultimate objective of CG is to ensure the shareholders’ wealth. A good corporate governance practice is regarded as an important aspect in reducing risks for investors, attracting capital for investment, and improving the performance of companies in the long run. The objective of this paper was to explore the relationship between the firms’ performance and corporate governance practices. The paper analysed board of directors and financial performance of major listed companies in the National Stock Exchange (NSE) S&P CNX Nifty during the study period. The study found that the corporate governance structure which incorporated government ownership created more opportunities and resources for better financial performance of the sample firms.